1998
DOI: 10.1038/sj.leu.2401067
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of the expression of Tdt and CD7 in 335 cases of acute myeloid leukemia

Abstract: We conclude that the expression of Tdt or CD7 is associated with an unfavorable outcome and that the combination of both defines a clinical subset with a poorer prognosis due to the significantly higher association with MDR phenotype, and 'poor prognostic' chromosomal abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 36 publications
7
59
4
Order By: Relevance
“…In our cases, there was a statistical significant relation between CD7aberrant expression and unfavorable cytogenetic pattern (p=0.046), in agreement with Ogata et al (2001) who found that the proportion of CD7+cases increased stepwise from the cases with favorable cytogenetics to the cases with intermediate and unfavorable cytogenetics, we support their recommendation that CD7 expression in AML should be interpreted in association with the cytogenetic. No statistical significance could be detected between CD7+AML and CD7-AML regarding CR or OS (p=0.68, 0.07 respectively) in agreement with Chang et al, (2007) but in contrast with Venditti et al, (1998) who reported that CD7 expression in AML adversely affect achievement of CR (p=0.013) and associated with shorter OS (p=0.006). This contradiction in the prognostic value of CD7in AML may be related to the fact that the cytogenetics status of the study population significantly skews the results where CD7 expression had no prognostic value if most examined cases had intermediate cytogenetics, while CD7+cases with unfavorable cytogenetics had an extremely poor prognosis (Ogata et al, 2001).…”
Section: 221 Clinical Significance Of Aberrant Antigens In Acute Leumentioning
confidence: 83%
See 1 more Smart Citation
“…In our cases, there was a statistical significant relation between CD7aberrant expression and unfavorable cytogenetic pattern (p=0.046), in agreement with Ogata et al (2001) who found that the proportion of CD7+cases increased stepwise from the cases with favorable cytogenetics to the cases with intermediate and unfavorable cytogenetics, we support their recommendation that CD7 expression in AML should be interpreted in association with the cytogenetic. No statistical significance could be detected between CD7+AML and CD7-AML regarding CR or OS (p=0.68, 0.07 respectively) in agreement with Chang et al, (2007) but in contrast with Venditti et al, (1998) who reported that CD7 expression in AML adversely affect achievement of CR (p=0.013) and associated with shorter OS (p=0.006). This contradiction in the prognostic value of CD7in AML may be related to the fact that the cytogenetics status of the study population significantly skews the results where CD7 expression had no prognostic value if most examined cases had intermediate cytogenetics, while CD7+cases with unfavorable cytogenetics had an extremely poor prognosis (Ogata et al, 2001).…”
Section: 221 Clinical Significance Of Aberrant Antigens In Acute Leumentioning
confidence: 83%
“…Aberrant antigen expression is reported to have variable frequency (Voskova et al, 2003;Vitale et al 2007;Zhang et al, 2012;Novoa et al, 2013) most commonly CD7 (Chang et al, 2007), CD9, CD19 and CD56 in AML cases (El-Sissy et al, 2006) as well as CD13 and CD33 in ALL (Liu et al, 2007;Suggs et al, 2007) and their prognostic and predictive relevance is controversial (Bhushan et al, 2010). However, several reports discussed their clinical significance, but most of them were not comprehensive (Putti et al, 1998;Venditti et al, 1998;Ogata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The particular marker combination was chosen because it is 1) widely used, 2) allows for an easy quantification of the marker expression on AML blasts and 3) was continuously used throughout the study period. Although TdT might be considered an unusual marker for AML, its correlation with blast immaturity is particularly strong [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AML patients with favorable cytogenetics [t(8;21), t(15;17), or inv(16)] generally expressed CD7 at a significantly lower rate than patients with other cytogenetic abnormalities. However, opposing opinions have also been approached by other researchers (10,12,13), highlighting the importance to perform more comprehensive studies in the future.…”
Section: Discussionmentioning
confidence: 99%